FRACTION IN ORDER SIMPLE DIFFERENTIAL EQUATIONS. IN CAPUTO'S SENSE FRACTION IN ORDER DIFFERENTIAL EQUATIONS FOR KOSHI ISSUE (American Journal of Public Diplomacy and International Studies (2993-2157), 2023)
Today's in the day differential equations and mathematics and physics equations directions wide spreading from directions one this fraction in order derivative and fraction are integral equations of order . Our life during many fields basically physics , chemistry , biology and etc in the fields processes fraction in order equations with expressing them _ in learning to us fraction in order equations help will give . In life many in processes them manage important importance occupation is enough For example , heat spread in the process something from the border the heat management